Polyarylamine hole transport material, synthetic method thereof and perovskite solar cell
By adopting the continuous cross-coupled C-N polycondensation method in the synthesis of polyarylamine hole transport materials, the problems of wide molecular weight distribution and poor batch repetition in the traditional method are solved, efficient synthesis and excellent batch consistency are achieved, and the efficiency of perovskite solar cells is improved.
Patent Information
- Application Number
- CN202411757542.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-18
AI Technical Summary
Existing functional conjugated polymers have challenges in mass production and maintaining batch consistency. Traditional C-C coupling polycondensation methods lead to wide distribution of molecular weights and generally greater than 2 polydispersity index and poor batch repeatability.
The continuous cross-coupled C-N polycondensation method is adopted, and the reaction activity of the intermediate is gradually adjusted through two continuous palladium-catalyzed C-N coupling cycles to achieve controlled polycondensation, thereby synthesizing polyaromatic amine hole transport material with excellent batch consistency.
The efficient synthesis of polyarylamine hole transport materials has been achieved, the performance consistency and structural stability of the material have been improved, and the photoelectric energy conversion efficiency of perovskite solar cells has been improved from 23.1% to 25.2%.
Smart Images

Figure CN119638984A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical and energy materials, and specifically relates to a preparation method of a polyarylamine hole transport material, a conversion mechanism of CN coupling polymerization thereof, and a perovskite solar cell constructed based on such material. Background Art
[0002] Despite the huge demand for functional conjugated polymers in the field of organic electronics, there are still severe challenges in achieving large-scale production and maintaining batch-to-batch consistency. In traditional CC coupling polycondensation, monomers are coupled in a less controlled manner in the initial stage to first generate a series of oligomers, which then react further to ultimately produce conjugated polymers with a wide molecular weight distribution and a polydispersity index generally greater than 2, with poor batch reproducibility. To this end, the present invention has developed a reaction activity-regulated continuous cross-coupling CN polycondensation method that can accurately synthesize functional polyarylamines with excellent batch consistency. The present invention reveals for the first time that the key to achieving controllable polycondensation through two consecutive palladium-catalyzed CN coupling cycles is to gradually adjust the reactivity of the intermediates. In addition, the present invention also strategically prepares a variety of polyarylamines to enhance the functionality of the materials, providing an effective polymerization method for conjugated polymers required for high-performance optoelectronic devices. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects in the prior art and provide a polyarylamine hole transport material and a synthesis method thereof and a perovskite solar cell, and to explore its conversion mechanism to efficiently construct a polyarylamine polymer through a one-step direct reaction of raw materials.
[0004] The specific technical solutions adopted by the present invention are as follows:
[0005] In the first aspect, the present invention provides a method for synthesizing a polyarylamine hole transport material, which is as follows:
[0006] Aromatic amine, aromatic halide, palladium catalyst, phosphine ligand and organic base are mixed and subjected to reflux reaction, and then a capping agent is added to terminate the reaction; the product is precipitated in methanol, and a solid is obtained by suction filtration, and a polyaromatic amine hole transport material is obtained after Soxhlet extraction.
[0007] Preferably, the aromatic amine is one or two of 2,4,6-trimethylaniline, 3,4,5-trimethoxyaniline, 4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]aniline, 4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]-2,6-dimethylaniline, 2,6-difluoro-4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]aniline, 4-aminobenzenesulfonamide and 3,5-dimethylpyridine-4-amine; the aromatic halide is one or two of 4,4′-dibromo-1,1′-biphenyl, 2,4′-dibromopyridine and 2,5-dibromopyridine.
[0008] Preferably, the palladium catalyst is one of tetrakis(triphenylphosphine)palladium, dichloro[1,1'-bis(diphenylphosphino)ferrocene]palladium, palladium acetate, (1,5-cyclooctadiene)palladium dichloride, bis(acetylacetone)palladium, tri(benzylideneacetone)dipalladium, bis(acetonitrile)palladium dichloride and palladium trifluoroacetate; the phosphine ligand is one of 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl, 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene, triphenylphosphine, 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl, 2-di-tert-butylphosphino-2',4',6'-triisopropylbiphenyl, tri-tert-butylphosphine tetrafluoroborate and 1,1'-binaphthyl-2,2'-bisdiphenylphosphine. Preferably, the organic base is one of polybis(ethoxypyrrolidone)phosphazene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, sodium tert-butoxide and potassium tert-butoxide.
[0009] Preferably, the mixed molar ratio of the aromatic amine, aromatic halide, palladium catalyst, phosphine ligand and organic base is 1:1:(0.02-0.1):(0.08-0.4):(2-5).
[0010] Preferably, the temperature of the reflux reaction is 65-130° C. and the reaction time is 24 h; the mixing molar ratio of the product after the reflux reaction to the end-capping agent is 0.02-0.2, the reaction time is 2 h, and the end-capping agent is one of bromobenzene, p-bromotoluene, 4-bromoanisole, 2-bromothiophene, 2-bromo-5-methylthiophene and 2-bromo-5-methoxythiophene.
[0011] In a second aspect, the present invention provides a polyarylamine hole transport material obtained by the synthesis method described in the first aspect, wherein the polyarylamine hole transport material is PTAA, PTATMA, PTAHOA, PTAMOA, PTAFOA, PDAPA, PTAMA, PTASA, PTAPA or PDAPA, and the specific chemical structural formulas are:
[0012]
[0013] In a third aspect, the present invention provides a perovskite solar cell based on the polyarylamine hole transport material of the second aspect, comprising a substrate, a transparent electrode layer, a hole transport layer, a perovskite layer, a fullerene electron transport layer, a hole blocking layer and a metal electrode layer arranged in layers from bottom to top;
[0014] The material of the hole transport layer is polyarylamine hole transport material or metal oxide / polyarylamine hole transport material; the metal oxide / polyarylamine hole transport material is a double-layer structure, the upper layer is polyarylamine hole transport material and the lower layer is metal oxide.
[0015] Preferably, the thickness of the polyarylamine hole transport material is 5-100 nm; the thickness of the metal oxide is 5-100 nm, and the material is one of nickel oxide, copper oxide, cuprous oxide, vanadium oxide, molybdenum oxide and tungsten oxide.
[0016] Preferably, the substrate material is glass or quartz or flexible PET or flexible PEN; the transparent electrode layer material is indium tin oxide or fluorine-doped tin oxide or a thin layer of metal with a thickness of 1-500nm; the thin layer of metal is silver or copper or gold.
[0017] Preferably, the perovskite layer is an ABX3 type metal halide material, A is an organic amine ion or an alkali metal ion, B is a divalent metal ion, and X is a halogen ion; the fullerene electron transport layer has a thickness of 50-100 nm.
[0018] Preferably, the hole blocking layer has a thickness of 5-10 nm; the metal electrode layer has a thickness of 1-300 nm, and the material is one of silver, aluminum, magnesium, copper, gold, indium tin oxide and fluorine-doped tin oxide.
[0019] In a fourth aspect, the present invention provides a method for preparing a perovskite solar cell, the process of which is as follows:
[0020] The glass substrate coated with indium tin oxide (ITO) was ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol, respectively. The ITO glass was then blown dry with dry nitrogen, and then the substrate was treated with ultraviolet ozone for 15 minutes to remove organic residues and impurities on the surface of the ITO glass. In a glove box, the polyarylamine hole transport material was spin-coated on the ITO substrate at a speed of 3500 rpm, and then annealed at 100°C for 30 minutes. The prepared perovskite solution (1.5 mol / L, the volume ratio of the solvent was DMF:DMSO=4:1) was spin-coated at a speed of 4000 rpm in the glove box, annealed at 100°C for 10 minutes, and then cooled. Then the prepared PCBM solution (20 mg / ml, CB as solvent) and BCP solution (1 mg / ml, ethanol as solvent) were spin-coated in the glove box at a speed of 3500 rpm. Finally, it was transferred to a vacuum lamination chamber (pressure of 5×10 -4 Pa) with a layer of about 100nm of Ag. At this point, the perovskite solar cell device is completed, and the device area is about 5.0mm 2 .
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a method for preparing a polyarylamine hole transport material, which realizes a more accurate and controllable polymerization process by precisely adjusting the reaction activity at each stage of the reaction, thereby improving the performance consistency and structural stability of the obtained product. Ten polyarylamine hole transport materials PTAA, PTATMA, PTAHOA, PTAMOA, PTAFOA, PDAPA, PTAMA, PTASA, PTAPA and PDAPA were prepared by a simple synthesis method. At the same time, by introducing a certain proportion of methoxy groups into the PTAA aromatic amine skeleton, the wettability of the PTAA hole transport film to polar solutions is improved, thereby improving the growth quality of the perovskite film. The lone pair electrons of the oxygen atoms act as Lewis bases to passivate the surface defects of the perovskite and enhance the chemical interaction force with the perovskite layer. It will be applied to perovskite solar cells, and the device efficiency will be increased from 23.1% to 25.2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the structure of the perovskite solar cell in the embodiment.
[0024] Figure 2 This is the current-voltage curve of the perovskite solar cell.
[0025] Figure 3 This is the H NMR spectrum of PTAA.
[0026] Figure 4 This is the molecular weight distribution spectrum of PTAA.
[0027] Figure 5 This is the H NMR spectrum of PTAMA.
[0028] Figure 6 This is the molecular weight distribution spectrum of PTAMA.
[0029] Figure 7 This is a diagram of the transformation mechanism of the palladium-catalyzed CN coupling reaction polymerization reaction.
[0030] The reference numerals in the figure are: substrate 1, transparent electrode layer 2, hole transport layer 3, perovskite layer 4, fullerene electron transport layer 5, hole blocking layer 6, and metal electrode layer 7. DETAILED DESCRIPTION
[0031] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0032] like Figure 7 As shown, the present invention provides a palladium-catalyzed CN coupling polymerization reaction, the conversion mechanism of which is that two consecutive catalytic cycles are achieved through reactive CN cross-coupling to accurately synthesize polyarylamines. In the first catalytic cycle, the highly reactive aromatic amine is initially coupled with an aromatic halide to form a bifunctional secondary aromatic amine intermediate (IM). In this process, the deprotonation of the aromatic amine (Ar2-NH2) undergoes a nucleophilic addition reaction with a Pd(II) complex to form Ar2-NH-Pd II -Ar1-Br intermediate. Subsequently, a reduction elimination reaction occurs to generate difunctional secondary aromatic amine IM with reduced reactivity. These intermediates remain dormant in the first catalytic cycle until the primary aromatic amine is completely consumed. The secondary aromatic amine intermediate and aromatic halide enter the second coupling polymerization catalytic cycle, achieving the precise synthesis of a series of polyaromatic amines with narrow molecular weight distribution.
[0033] Based on the above transformation mechanism principle, the present invention uses triarylamine as the skeleton and develops a series of aromatic amine polymers through palladium-catalyzed CN coupling. The general synthesis reaction equations of polyaromatic amine hole transport materials PTAA, PTATMA, PTAHOA, PTAMOA, PTAFOA, PDAPA, PTAMA, PTASA, PTAPA and PDAPA are shown below. Among them, aromatic amine and aromatic halide monomers are purchased through commercial channels.
[0034]
[0035] The present invention provides a method for synthesizing a polyarylamine hole transport material, which is specifically as follows:
[0036] Aromatic amine, aromatic halide, palladium catalyst, phosphine ligand and organic base are added into a dry reaction bottle, mixed and refluxed, and then a capping agent is added to terminate the reaction; the product is precipitated in methanol, filtered to obtain a solid, and then subjected to Soxhlet extraction to obtain a polyaromatic amine hole transport material.
[0037] In actual use, the reaction can realize the coupling polymerization of various aromatic amines and aromatic halides, for example: binary polymers: synthesized from different aromatic amines and aromatic halides; ternary polymers: synthesized from two different aromatic amines and aromatic halides; ternary polymers: synthesized from one aromatic amine and two different aromatic halides, and from one aromatic halide and two different aromatic amines.
[0038] As a preferred embodiment of the present invention, the aromatic amine is one or two of 2,4,6-trimethylaniline, 3,4,5-trimethoxyaniline, 4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]aniline, 4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]-2,6-dimethylaniline, 2,6-difluoro-4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]aniline, 4-aminobenzenesulfonamide and 3,5-dimethylpyridine-4-amine.
[0039] As a preferred embodiment of the present invention, the aryl halide is one or two of 4,4'-dibromo-1,1'-biphenyl, 2,4'-dibromopyridine and 2,5-dibromopyridine.
[0040] As a preferred embodiment of the present invention, the palladium catalyst is one of tetrakistriphenylphosphine palladium, dichloro[1,1'-bis(diphenylphosphino)ferrocene]palladium, palladium acetate, 1,5-cyclooctadiene palladium dichloride, diacetylacetonate palladium, tribenzylideneacetone dipalladium, diacetonitrile palladium dichloride and palladium trifluoroacetate; the phosphine ligand is one of 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl, 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene, triphenylphosphine, 2-dicyclohexylphosphino-2',6'-dimethoxybiphenyl, 2-di-tert-butylphosphino-2',4',6'-triisopropylbiphenyl, tri-tert-butylphosphine tetrafluoroborate and 1,1'-binaphthyl-2,2'-bisdiphenylphosphine.
[0041] As a preferred embodiment of the present invention, the organic base is one of polybis(ethoxypyrrolidone)phosphazene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, sodium tert-butoxide and potassium tert-butoxide.
[0042] As a preferred embodiment of the present invention, the mixed molar ratio of aromatic amine, aromatic halide, palladium catalyst, phosphine ligand and organic base is 1:1:0.02-0.1:0.08-0.4:2-5. Further, the mixed molar ratio of aromatic amine, aromatic halide, palladium catalyst, phosphine ligand and organic base is 1:1:0.02:0.08:3.
[0043] As a preferred embodiment of the present invention, the temperature of the reflux reaction is 65-130° C. and the reaction time is 24 hours; the mixing molar ratio of the product after the reflux reaction to the end-capping agent is 0.02-0.2, the reaction time is 2 hours, and the end-capping agent is one of bromobenzene, p-bromotoluene, 4-bromoanisole, 2-bromothiophene, 2-bromo-5-methylthiophene and 2-bromo-5-methoxythiophene.
[0044] The polyarylamine hole transport material prepared by the present invention is PTAA, PTATMA, PTAHOA, PTAMOA, PTAFOA, PDAPA, PTAMA, PTASA, PTAPA or PDAPA, and the specific chemical structural formulas are:
[0045]
[0046] like Figure 1 As shown, the present invention provides a perovskite solar cell based on the above-mentioned polyarylamine hole transport material, and the perovskite solar cell comprises a substrate 1, a transparent electrode layer 2, a hole transport layer 3, a perovskite layer 4, a fullerene electron transport layer 5, a hole blocking layer 6 and a metal electrode layer 7 arranged in layers from bottom to top. Among them, the material of the hole transport layer 3 is a polyarylamine hole transport material or a metal oxide / polyarylamine hole transport material; the metal oxide / polyarylamine hole transport material is a double-layer structure, the upper layer is a polyarylamine hole transport material, and the lower layer is a metal oxide.
[0047] As a preferred embodiment of the present invention, the thickness of the polyarylamine hole transport material is 5-100 nm; the thickness of the metal oxide is 5-100 nm, and the material is one of nickel oxide, copper oxide, cuprous oxide, vanadium oxide, molybdenum oxide and tungsten oxide.
[0048] As a preferred embodiment of the present invention, the substrate 1 is made of glass or quartz or flexible PET or flexible PEN.
[0049] As a preferred embodiment of the present invention, the material of the transparent electrode layer 2 is indium tin oxide or fluorine-doped tin oxide or a thin layer of metal with a thickness of 1-500 nm; the thin layer of metal is silver or copper or gold.
[0050] As a preferred embodiment of the present invention, the perovskite layer 4 is an ABX3 type metal halide material, A is an organic amine ion or an alkali metal ion, B is a divalent metal ion, and X is a halogen ion.
[0051] As a preferred embodiment of the present invention, the thickness of the fullerene electron transport layer 5 is 50-100 nm.
[0052] As a preferred embodiment of the present invention, the hole blocking layer 6 has a thickness of 5-10 nm.
[0053] As a preferred embodiment of the present invention, the thickness of the metal electrode layer 7 is 1-300 nm, and the material is one of silver, aluminum, magnesium, copper, gold, indium tin oxide and fluorine-doped tin oxide.
[0054] The synthesis method of the present invention and the properties of the obtained materials are described below through specific examples.
[0055] Example 1
[0056] Under argon protection, 2,4,6-trimethylaniline (2.96mmol, 400.0mg), 4,4′-dibromo-1,1′-biphenyl (2.96mmol, 923.0mg), phosphine ligand (0.47mmol), organic base (6.51mmol) and 10ml toluene were placed in a Schlenk vacuum sealed bottle, frozen with liquid nitrogen, and then three cycles of vacuuming and filling with argon were performed. Palladium catalyst (0.12mmol) was added, and the mixture was frozen and refluxed three times. The mixture was heated at 110°C for 24h, and 0.05 molar equivalent of bromobenzene was added and reacted for 2h. After the reaction was completed, the reaction solution was dropped into methanol for precipitation, and the precipitated solid was obtained by suction filtration. PTAA was obtained by Soxhlet extraction with methanol, acetone and chloroform.
[0057] The reaction process is as follows:
[0058]
[0059] The NMR spectrum of PTAA prepared in this example is as follows: Figure 3 As shown in the figure, it can be seen that 1 HNMR (500MHZ,CDCl3)δ:7.41-7.39(d,J=8.6Hz,4H),7.04-7.02(d,J=8.5Hz,4H),6.96(s,2H),2.34(s,3H),2.03(s,6H). Molecular weight distribution spectrum is shown in Figure 4 As shown in the figure, it can be seen that M n =25.7 kDa, M w =39.9 kDa,
[0060] Example 2
[0061] Under argon protection, 2,4,6-trimethylaniline (2.22mmol, 300.0mg), 3,4,5-trimethoxyaniline (0.25mmol, 45.2mg), 4,4′-dibromo-1,1′-biphenyl (2.47mmol, 769.2mg), phosphine ligand (0.36mmol), organic base (5.42mmol) and 10ml toluene were placed in a Schlenk vacuum sealed bottle, frozen with liquid nitrogen, and then three cycles of vacuuming and filling with argon were performed. Palladium catalyst (0.09mmol) was added, and the mixture was frozen and refluxed three times. The mixture was heated at 110°C for 24h, and 0.05 molar equivalent of bromobenzene was added and reacted for 2h. After the reaction was completed, the reaction solution was dropped into methanol for precipitation, and the precipitated solid was obtained by suction filtration. PTAMA was obtained by Soxhlet extraction with methanol, acetone and chloroform.
[0062] The reaction process is as follows:
[0063]
[0064] The NMR spectrum of PTAMA prepared in this example is as follows: Figure 5 As shown in the figure, it can be seen that 1 HNMR (400MHZ,CDCl3)δ:7.48-7.35(m,4H),7.10-6.91(m,6H),6.38(s,0.1H),3.86(s,0.2H),3.72(s,0.4H),2.35(s,3H),2.04(s,6H). Molecular weight distribution spectrum is shown in Figure 6 As shown in the figure, it can be seen that M n =9.3kDa,M w =17.5 kDa,
[0065] Example 3
[0066] The glass substrate coated with indium tin oxide (ITO) was ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol, respectively. The ITO glass was then blown dry with dry nitrogen, and the substrate was treated with ultraviolet ozone for 15 minutes to remove organic residues and impurities on the surface of the ITO glass. In a glove box, PTAA (the material obtained by the preparation method of Example 1) with a concentration of 1 mg / ml was spin-coated on the ITO substrate at a speed of 3500 rpm, and then annealed at 100°C for 30 minutes. The prepared perovskite solution (1.5 mol / L, the volume ratio of the solvent is DMF:DMSO=4:1) was spin-coated at a speed of 4000 rpm in the glove box, annealed at 100°C for 10 minutes, and then cooled. Then the prepared PCBM solution (20 mg / ml, CB as solvent) was spin-coated at a speed of 3500 rpm in the glove box. Finally, it was transferred to a vacuum lamination chamber (pressure of 5×10 -4 Pa) with a layer of about 100nm of Ag. At this point, the perovskite solar cell device is completed, and the device area is about 5.0mm 2 The current-voltage curve test results are as follows: Figure 2 As can be seen from the figure, the open circuit voltage of the perovskite solar cell is 1.18V and the short circuit current density is 24.3mA / cm 2 , the filling factor is 0.81, and the photoelectric energy conversion efficiency is 23.1%.
[0067] Example 4
[0068] The glass substrate coated with indium tin oxide (ITO) was ultrasonically cleaned with detergent, deionized water, acetone, and isopropanol, respectively. The ITO glass was then blown dry with dry nitrogen, and the substrate was treated with ultraviolet ozone for 15 minutes to remove organic residues and impurities on the surface of the ITO glass. In a glove box, PTAMA (the material obtained by the preparation method of Example 2) with a concentration of 1 mg / ml was spin-coated on the ITO substrate at a speed of 3500 rpm, and then annealed at 100°C for 30 minutes. The prepared perovskite solution (1.5 mol / L, the volume ratio of the solvent is DMF:DMSO=4:1) was spin-coated at a speed of 4000 rpm in the glove box, annealed at 100°C for 10 minutes, and then cooled. Then the prepared PCBM solution (20 mg / ml, CB as solvent) was spin-coated at a speed of 3500 rpm in the glove box. Finally, it was transferred to a vacuum lamination chamber (pressure of 5×10 -4 Pa) with a layer of about 100nm of Ag. At this point, the perovskite solar cell device is completed, and the device area is about 5.0mm 2 The current-voltage curve test results are as follows: Figure 2 As can be seen from the figure, the open circuit voltage of the perovskite solar cell is 1.21V and the short circuit current density is 24.7mA / cm 2, the filling factor is 0.84, and the photoelectric energy conversion efficiency is 25.2%.
[0069] At a light intensity of 100 mW / cm 2 The current-voltage curves of the perovskite solar cells obtained in Example 3 and Example 4 were tested under AM 1.5G simulated sunlight. As can be seen from the figure, the open circuit voltage of the device in Example 3 based on the PTAA hole transport layer is 1.18V, and the short circuit current density is 24.3mA / cm 2 , the fill factor is 0.81, and the photoelectric energy conversion efficiency is 23.1%. The open circuit voltage of the device of Example 4 based on the PTAMA hole transport layer is 1.21V, and the short circuit current density is 24.7mA / cm 2 , the filling factor is 0.84, and the photoelectric energy conversion efficiency is 25.2%.
[0070] It can be seen that based on the PTAA polyarylamine skeleton, the introduction of a certain proportion of methoxy groups improves the wettability of the PTAA hole transport film to polar solutions, thereby improving the growth quality of the perovskite film. The lone pair of electrons of the oxygen atom acts as a Lewis base to coordinate with the lead ions of the perovskite, passivating the surface defects of the perovskite. The prepared device has a high open circuit voltage V OC and short-circuit current J SC , and obtain higher device efficiency.
[0071] The present invention synthesizes a series of polyaromatic amines through the carbon-nitrogen (CN) coupling polymerization reaction of aromatic amines and aromatic halides. It is different from the traditional single catalytic cycle carbon-carbon (CC) coupling polymerization process. The present invention realizes two continuous CN cross-coupling catalytic cycles by adjusting the activity of the reaction intermediates, that is, in the first catalytic cycle, the highly reactive aromatic amine is coupled with the aromatic halide to generate a low-activity bifunctional secondary aromatic amine intermediate, and the intermediate remains dormant in the first catalytic cycle until the primary aromatic amine is completely consumed, and then the secondary aromatic amine intermediate is coupled with the aromatic halide to achieve the precise synthesis of a series of molecular weight narrow distribution polyaromatic amines. This type of polyaromatic amine can be used as a hole transport material to construct a perovskite solar cell, regulate interface hole extraction and promote perovskite growth. The perovskite solar cell includes a substrate, a transparent electrode layer, a hole transport layer, a perovskite layer, a fullerene electron transport layer, a hole blocking layer, and a metal electrode. The perovskite solar cell prepared by the present invention has an open circuit voltage of 1.21V and a short circuit current density of 24.7mA / cm 2 , the filling factor is 0.84, and the photoelectric energy conversion efficiency is 25.2%.
[0072] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for synthesizing a polyarylamine hole transport material, characterized in that: The details are as follows: Aromatic amine, aromatic halide, palladium catalyst, phosphine ligand and organic base are mixed and subjected to reflux reaction, and then a capping agent is added to terminate the reaction; the product is precipitated in methanol, and a solid is obtained by suction filtration, and a polyaromatic amine hole transport material is obtained after Soxhlet extraction.
2. The method for synthesizing a polyarylamine hole transport material according to claim 1, characterized in that: The aromatic amine is one or two of 2,4,6-trimethylaniline, 3,4,5-trimethoxyaniline, 4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]aniline, 4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]-2,6-dimethylaniline, 2,6-difluoro-4-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]aniline, 4-aminobenzenesulfonamide and 3,5-dimethylpyridine-4-amine; the aromatic halide is one or two of 4,4′-dibromo-1,1′-biphenyl, 2,4′-dibromopyridine and 2,5-dibromopyridine.
3. The method for synthesizing a polyarylamine hole transport material according to claim 1, characterized in that: The palladium catalyst is one of tetrakis(triphenylphosphine)palladium, dichloro[1,1'-bis(diphenylphosphino)ferrocene]palladium, palladium acetate, (1,5-cyclooctadiene)palladium dichloride, bis(acetylacetone)palladium, tri(benzylideneacetone)dipalladium, bis(acetonitrile)palladium dichloride and palladium trifluoroacetate; the phosphine ligand is 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl, 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene, triphenylphosphine, ... The organic base is one of 2′,6′-dimethoxy-2′-butylphosphino-biphenyl, 2-di-tert-butylphosphino-2′,4′,6′-triisopropylbiphenyl, tri-tert-butylphosphine tetrafluoroborate and 1,1′-binaphthyl-2,2′-bisdiphenylphosphine; the organic base is one of polybis(ethoxypyrrolidone)phosphazene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, sodium tert-butoxide and potassium tert-butoxide.
4. The method for synthesizing a polyarylamine hole transport material according to claim 1, characterized in that: The mixing molar ratio of the aromatic amine, the aromatic halide, the palladium catalyst, the phosphine ligand and the organic base is 1:1:(0.02-0.1):(0.08-0.4):(2-5).
5. The method for synthesizing a polyarylamine hole transport material according to claim 1, characterized in that: The temperature of the reflux reaction is 65-130° C. and the reaction time is 24 hours. The mixing molar ratio of the product after the reflux reaction to the end-capping agent is 0.02-0.2, and the reaction time is 2 hours. The end-capping agent is one of bromobenzene, p-bromotoluene, 4-bromoanisole, 2-bromothiophene, 2-bromo-5-methylthiophene and 2-bromo-5-methoxythiophene.
6. A polyaromatic amine hole transport material obtained by the synthesis method according to claims 1 to 5, characterized in that: The polyarylamine hole transport material is PTAA, PTATMA, PTAHOA, PTAMOA, PTAFOA, PDAPA, PTAMA, PTASA, PTAPA or PDAPA, and the specific chemical structural formulas are:
7. A perovskite solar cell based on the polyarylamine hole transport material according to claim 6, characterized in that: The invention comprises a substrate (1), a transparent electrode layer (2), a hole transport layer (3), a perovskite layer (4), a fullerene electron transport layer (5), a hole blocking layer (6) and a metal electrode layer (7) which are arranged in layers from bottom to top; the material of the hole transport layer (3) is a polyaromatic amine hole transport material or a metal oxide / polyaromatic amine hole transport material; the metal oxide / polyaromatic amine hole transport material is a double-layer structure, wherein the upper layer is the polyaromatic amine hole transport material and the lower layer is the metal oxide.
8. The perovskite solar cell according to claim 7, characterized in that: The thickness of the polyarylamine hole transport material is 5-100nm; the thickness of the metal oxide is 5-100nm, and the material is one of nickel oxide, copper oxide, cuprous oxide, vanadium oxide, molybdenum oxide and tungsten oxide.
9. The perovskite solar cell according to claim 7, characterized in that: The substrate (1) is made of glass or quartz or flexible PET or flexible PEN; the transparent electrode layer (2) is made of indium tin oxide or fluorine-doped tin oxide or a thin layer of metal with a thickness of 1-500 nm; the thin layer of metal is silver or copper or gold; the perovskite layer (4) is an ABX3 type metal halide material, A is an organic amine ion or an alkali metal ion, B is a divalent metal ion, and X is a halogen ion; the fullerene electron transport layer (5) has a thickness of 50-100 nm.
10. The perovskite solar cell according to claim 7, characterized in that: The hole blocking layer (6) has a thickness of 5-10 nm; the metal electrode layer (7) has a thickness of 1-300 nm, and the material is one of silver, aluminum, magnesium, copper, gold, indium tin oxide and fluorine-doped tin oxide.
Citation Information
Patent Citations
Use of triarylamine derivatives as hole-conducting materials in organic solar cells and organic solar cells containing said triarylamine derivatives
CN102326271A
Hole injection layer and hole-transporting layer
CN105514272A
Perovskite thin film with two-dimensional and three-dimensional multilevel structure and method and application of perovskite thin film
CN115172614A
Triphenylamine polymer hole transport material applied to trans-perovskite solar cell
CN115991862A
Polymer semiconductor material containing benzene or pyridine ethynyl triphenylamine, hole transport material formed by crosslinking of polymer semiconductor material and application of polymer semiconductor material
CN117924671A
Cited By
Palladium catalyst and preparation method and application thereof
CN120737130A
PTAA copolymer with photo-thermal stability and preparation method thereof
CN122011344A